2021
DOI: 10.1111/ene.14701
|View full text |Cite
|
Sign up to set email alerts
|

Signs of spatial neglect in unilateral peripheral vestibulopathy

Abstract: Background and purpose In this study, the question of whether egocentric representation of space is impaired in chronic unilateral vestibulopathies was examined. The objective was to test current theories attributing a predominant role to vestibular afferents in spatial cognition and to assess whether representational neglect signs are common in peripheral vestibular loss. Methods The subjective straight‐ahead (SSA) direction was investigated using a horizontal rod allowing the translation and rotation compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…Such ‘body referencing’ has also been reported in human functional imaging studies (e.g. Bottini et al, 2001 ; Galati et al, 2010 ; Schindler and Bartels, 2013 ; Saj et al, 2020 ). It thus is conceivable that tonic MVS (as well as CVS, etc.)…”
Section: Discussionsupporting
confidence: 56%
“…Such ‘body referencing’ has also been reported in human functional imaging studies (e.g. Bottini et al, 2001 ; Galati et al, 2010 ; Schindler and Bartels, 2013 ; Saj et al, 2020 ). It thus is conceivable that tonic MVS (as well as CVS, etc.)…”
Section: Discussionsupporting
confidence: 56%
“…Such "body referencing" has also been reported in human functional imaging studies (e.g. Bottini et al 2001, Galati et al 2010, Schindler & Bartels 2013, Saj et al 2020. It thus is conceivable that tonic MVS (as well as CVS, etc.)…”
Section: Discussionsupporting
confidence: 54%
“…Our data show that the consequences of the neurotomy depend on the preoperative status of the patients. Before the neurotomy, the level of the vestibulopathy differed from one patient to another, and the data showed that the greater the vestibular loss, the greater the translation error at this preoperative stage (Saj et al, 2021 ). In this study, from the analyses presented, we can add that the lower was the translation error before the neurotomy, the greater was its increase 2 months later when all patients had a total unilateral vestibular loss.…”
Section: Discussionmentioning
confidence: 99%
“…Each gave informed consent to this study, which was approved by the local ethics committee. The egocentric representation of space of the participants at D –1 has been described in a preliminary study by Saj et al ( 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation